Popularyzacja wiedzy na temat specyfiki rozwojowej okresu adolescencji w środowisku rodzinnym - Peret-Drążewska, Paulina (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
The period of adolescence is a time of changes taking place on many dimensions of the functioning of young people. One of them is transformations in functioning in the family environment, which results from the need to realign parent-adolescent relationships. This task is mainly on the side of adults. Therefore, it seems important in this respect to know the psychosocial mechanisms and developmental tasks of the adolescence period.
Keywords: youth; upbringing; development; family